EFFECT OF DIFFERENT FERTILITY LEVELS AND NUTRIENT UPTAKE BY DROUGHT TOLERANT RICE GENOTYPES UNDER RAINFED CONDITION - TRIPTI NAYAK AND V. N. MISHRA, TRIBHUVAN PATEL, (The Bioscan, 2015)
An ongoing field experiment was conducted to study the effect of different fertility levels on N, P, K and micro nutrient uptake by drought tolerant rice genotypes under rain fed condition at IGKV, Raipur.The Soil of experimental field’s soil exhibited neutral reaction (pH 7.34), EC 0.26 (dSm-1), medium status of organic C (0.58%), low in available N (273 kg ha-1), medium in P (14.78 kg ha-1), high in K status (616 kg ha-1) and sufficient level in micronutrients (Fe, Mn, Cu, & Zn).Result showed that the overall average nutrients use efficiencies for N, P and K were recorded as 35.69, 18.41 and 112.75 per cent, respectively. Rice genotype R-RF-65 registered the nutrients use efficiencies for N, P and K ranged as 43.55-35.65, 23.65-20.15 and 165.60-92.50, respectively. Nutrient use efficiencies were observed higher at low fertility level and vice versa. Potassium use efficiency showed very high values which was due to less crop response to the applied K fertilizer. Most of the genotypes tested for their nutrient use efficiencies performed better than local check. The crop season was favorable and no water stress occurred during entire period which favored the genotypes to perform their potential level.